Model Dakwah Kultural di Masyarakat Adat dalam Penerapan Nilai-nilai Islam: (Studi Kasus Masyarakat Adat Cisungsang, Banten) - Abdul Muiz; Aji Sumiaji (STID DI AL-HIKMAH, 2015)
Cisungsang Indigenous Peoples is an agrarian society that lived at the foot of Mountain Mist, they are Muslims, but they mingled with Hindu and Buddhist culture they bring from their places of origin, namely the Kingdom of Padjadjaran, many of these cultures that do not fit even deviate from the teachings of Islam either or perakteknya. So, with all the potential preachers preaching try to change Hindu and Buddhist culture of the indigenous peoples with the Islamic values ??using Cultural Propagation Model. This study used a qualitative approach is a model of humanistic studies (humanity), which puts humans as the main subject in the event of social/cultural and descriptive research type is the type of research that includes a description on a situation as clear as possible, without any treatment of the object under study, whereas Data collection method using observational methods, namely direct observation research location. In addition, the method used is the interview conducted with perpetrators of propaganda and public figures.